Effect of Core Stability Exercise on Lower Back Pain of Fish Boilers In Sentra of Kusamba's Boiling Place - Ni Putu Diah Ayu Rusmeni -; I Dewa Ayu Rismayanti; I Kadek Yudi Aryawan (Jurnal Kesehatan dr. Soebandi, 2025)
Low back pain (LBP) is pain felt in the lower back area, it can be local pain or racular pain or both. Core stability is a very important exercise to maintain stability and blood balance in the spine to the pelvic bone, core stability is effective in improving the ability to maintain position and movement from the trunk to the pelvis which is useful for moving, controlling pressure and movement during activities. This study aims to determine the effect of core stability exercise on lower back pain in fish workers at Sentra of Kusamba's Boiling Place. This type of research is a pre-experimental with a pre-post test one group design, the test used Wilcoxon signed rank test with a Bourbonnis pain scale observation sheet research instrument. The sample in this study was 67 respondents with a non-probability sampling technique with inclusion criteria, namely laborers/workers at Kusamba's Boiling Place aged 20-75 with mild to moderate pain, willing to be respondents, and willing to follow the exercises given. The results of the study showed that the average pre-test pain intensity was 5,39, after being given core stability exercise treatment, the average pain intensity was 2,60. The results of data analysis using the Wilcoxon signed rank test obtained a value of (0.001) or p <α (0.05). There is an influence between core stability exercise and lower back pain in Sentra of Kusamba's Boiling Place.